Customer Protection Through Implementation Of Banking Governance - Utari, Anak Agung Dewi; Imaniyati, Neni; Kartono, Kartono (SEAN Institute, 2024)
The number of banks closing is a phenomenon considering the role of banking in economic growth. GCG is the main requirement for banking existence in carrying out its intermediary function. This research aims to examine the relationship between contract balance and banking health and uses a normative juridical research form with a statutory regulation approach and a multidisciplinary approach involving the theory of economic analysis of laws and civil law and governance. The analysis emphasizes non-juridical research. The research results show that implementation of good corporate governance by prioritizing balanced contracts between the parties. The position of banking institutions can continue to be maintained if supervision from the OJK institution and the implementation of good governance based on applicable regulations run as they should. So far, many banks have gone bankrupt due to fraud and mismanagement, especially in corporate governance, even though the OJK has tried to restore banking health. Imbalance in contracts is also a form of bank non-transparency in contracts with customers, resulting in high NPLs that can affect the liquidity risk of bank financial institutions